Повстансько-партизанський рух на Нікопольщині у часи Української революції 1917–1921 років - Зайцев, С. (Краєзнавство, 2020)
Здійснено спробу висвітлити особливості повстансько-партизанського руху на території сучасного Нікопольського району в період Української революції 1917–1921 рр. Визначено його головні рушійні сили. Виділено основні етапи та напрями повстансько-партизанської боротьби.Розглянуто найважливіші події в історії діяльності повстанських і партизанських загонів, відтворено перебіг бойових операцій. The purpose of the study is to analyze the features of the rebel-partisan movement in the territory of modern Nikopol region during the Ukrainian Revolution of 1917–1921, determination its main driving forces, elucidation main directions of their activity. The methodology of the researchis based on the principles of historicism, objectivity and social approach. Of the general scientific methods have beenused the following: analytical, classification, analogy and comparative. Also, general-historical methods have been used such as: problem-chronological, periodization, comparative- historical and typological. The originality of the study is determined by the fact that for the first comprehensively explores the problem, which activities of irregular combat units in the Nikopol region in the 1917–1920s relates, by the basis of a wide range of published sources, unpublished documents and memoirs of eyewitnesses. As a result of research the main driving forces of the rebel-partisan movement in the territory of Nikopol region in the mentioned period are defined. These were Bolshevik, pro-Ukrainian, anarchist and apolitical military formations.The main stages and directions of this movement are established. The most important events in the history of the activities of insurgent and partisan units are discussed, the course of combat operations is restored. Further research on this topic will allow deeper and more detailed disclosure of the history as Katerinoslav region in particular, and Ukraine as a whole.